Hubungan Durasi Bermain Online Games dengan Gangguan Tidur pada Pelajar SMA Mardisiswa di Era Pandemi COVID-19 - Meuthia Rahmawati; Yuni Wijayanti (Universitas Airlangga, 2023)
Background: Sleep disorders are disorders that refer to conditions that affect the quality, timing, or duration of sleep. Sleep disorders experienced by adolescents can contribute to medical problems and some mental health problems. There are around 73.7% of the population or the equivalent of 196.7 million internet users in Indonesia. One part of the internet that has influenced human life is online games. Objectives: to determine out the relationship between the duration of playing online games and sleep disturbances among Mardisiswa high school students during the COVID-19 pandemic. Methods: This research uses the type of analytic observational research. This cross-sectional study involved 72 students at SMA Mardisiswa who took the sample using the proportional random sampling method. The data collection process was carried out by distributing questionnaires online using the Google form. The variables measured were the duration of playing online games and sleep disturbance variables using the PSQI questionnaire. To analyze the data, the Fisher test was used. The independent variable is the duration of playing online games and the dependent variable is sleep disturbance. Results: The results of the study show that there is a relationship between the duration of playing online games and sleep disturbances in students. This is shown by the results of the study using the Fisher test, namely p value (0.004) <α (0.05). PR value of 6.4 with 95% CI 1.82-22.53, indicating that students with a duration of playing online games two hours or more have a risk of sleep disturbance 6.4 times greater than students with duration of playing online games less than two hours. Conclusions: Research concludes that the duration of playing online games and sleep disturbances are related or related. Therefore, it is necessary to have data regarding sleep disturbances and supported by socialization regarding this matter to teachers, parents and students.